The Deadly Dungeon - Roy, Ron 1940-; Gurney, John (New York : Random House, 1998)
While visiting Wallis's castle, Dink and his friends investigate strange noises that lead them to a dangerous secret.
"A Stepping Stone book."
"grades 2-4"--cover p. [4].
Keywords: Castles -- Fiction; Fiction